The Development of Youth Morality In The Millennial Era: A Theological Review of Youth Morality In Mandolang Satu, Minahasa Based on The Characters of Jeremiah and Timothy - Nontje Mery Timbuleng (Green Publisher Indonesia, 2024)
The development of the morality of young Christians in the Mandolang Satu area still shows some engaging in free association, leading them to fall into promiscuity, drug abuse, and excessive drinking. The research aims to highlight and describe the characters of millennial youth shaped within Christian family life and to examine the exemplary figures in the Bible that impact the moral development of millennial youth. This study employs a qualitative method, where the researcher acts as the primary instrument and adapts to the typical situations regarding the collection of predominantly qualitative data. The researcher will describe various perspectives and experiences of informants regarding their moral development based on Christian moral norms and principles, compared to the examples set by Jeremiah and Timothy. Data collection techniques include observation, interviews, and documentary studies. The research findings conclude that the character of millennial youth is shaped from childhood and carries on into adulthood within Christian family life. The examples set by Jeremiah and Timothy in the Bible have positive impacts on the moral development of millennial youth but are still limited to understanding and not yet practiced in daily life. The moral development of young people in the millennial era is declining due to societal changes, and free association is considered acceptable, making it difficult for parents and the church to transform the character of millennial youth who no longer follow the examples of Jeremiah and Timothy.